Innovative development of the export- and raw-material-oriented region - Golub, A.A.; Medebayeva, A.B. (BUKETOV BUSINESS REVIEW, 2017)
The East Kazakhstan region of the Republic of Kazakhstan with the prevailing share of mining and metallur- gical production is one of the main industrial regions of the country. The territory of the region has a large share of the mining and smelting industry concentrated, as well as the domestic engineering enterpris- es. Within the framework of this article, the general social and economic situation of the East Kazakhstan re- gion will be analyzed with determination of the mining sector role in the regional economy. There are many models of innovative development. Thus, it is suggested to propose an innovative development model of the region taking into account the economic specifics of the region. The abstract is devoted to the need for eco- nomic growth and the welfare of the region through the innovative activities development. The need for inno- vative development of the economy of the export- and raw-material-oriented region is due to the problems of domestic social and economic development related to low growth rates of the gross regional product, a notable drop in quality and living standards, an unfavorable environmental situation, and a growing popula- tion outflow outside the region. Some aspects of the social and economic situation of the East Kazakhstan re- gion have been reviewed, and a model of innovative development has been proposed with due account for the specifics of the regional economy. Taking into account the specifics of the region, the challenges requir- ing solution have been identified. At the same time, the conditions to facilitate the establishment of innova- tion-driven economy of the region have been defined.